Harmonizing genetic type and environmental level in dual-purpose cattle herds in Latin America - Vaccaro, L.=700 1 Vaccaro, R.; Verde, O.; Mejias, H.; Rios, L.; Romero, E.
(Fr, Es)
Ilus., 9 ref.
Keywords: GANADO BOVINO; VARIACION GENETICA; FACTORES AMBIENTALES; GANADO; RAZAS MIXTAS; AMERICA LATINA; REVISTA MUNDIAL DE ZOOTECNIA